2014
DOI: 10.1111/1346-8138.12440
|View full text |Cite
|
Sign up to set email alerts
|

Thymus and activation‐regulated chemokine as a clinical biomarker in atopic dermatitis

Abstract: Thymus and activation-regulated chemokine (TARC/CCL17) is a member of the T-helper 2 chemokine family. In Japan, serum TARC level has been commercially measured since 2008. After years of experience, we realized that TARC is an extremely useful clinical biomarker for atopic dermatitis (AD) treatment. Usually, physicians conduct a visual examination to determine whether their treatment has been successful; however, the visual examination results may not always be accurate; in such cases, serum TARC levels shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 35 publications
2
123
2
4
Order By: Relevance
“…Finally, the CCL17/TARC level (pg/mL), known to be associated with AD severity [14], decreased from baseline to week 16 in the GM080 treatment group from 186.58 ± 364.84 (mean ± SD) to 133.94 ± 270.42 and in the placebo group from 220.64 ± 385.42 to 128.37 ± 238.53. Taken together, this was a significant decrease for the overall population ( p = 0.017), but no significant difference was observed between the two treatment groups ( p = 0.990).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the CCL17/TARC level (pg/mL), known to be associated with AD severity [14], decreased from baseline to week 16 in the GM080 treatment group from 186.58 ± 364.84 (mean ± SD) to 133.94 ± 270.42 and in the placebo group from 220.64 ± 385.42 to 128.37 ± 238.53. Taken together, this was a significant decrease for the overall population ( p = 0.017), but no significant difference was observed between the two treatment groups ( p = 0.990).…”
Section: Resultsmentioning
confidence: 99%
“…High serum TARC level indicates accelerated pathogenesis of skin inflammation. Recently, TARC level is being used as a biomarker for AD treatment [32,33]. Also, it was reported to significantly correlate with barrier function even in mild AD [34].…”
Section: Discussionmentioning
confidence: 99%
“…14, 15 Recently, Lee et al found that CCL17 gene polymorphisms and their expression were associated with susceptibility and the formation of coronary artery aneurysms in Kawasaki disease. 16 Several previous studies have reported that the CCL17 SNP rs223828 (previously known as −431C>T) is associated with increased CCL17 expression.…”
Section: Effects Of Ccl17 Snp Rs223828 On Ccl17 Promoter Activitymentioning
confidence: 99%